2021
DOI: 10.1515/jom-2020-0106
|View full text |Cite
|
Sign up to set email alerts
|

First-time sports-related concussion recovery revisited: management changes and impact on recovery

Abstract: Context Concussion is among the most common injuries in athletes. Over the past 10 years, concussion knowledge has expanded, and guidelines for management have changed. Recent changes include recommendations against strict mental and physical rest after sustaining a concussion, a better recognition of preexisting conditions predisposing protracted concussion recovery, and the addition of preliminary patient counseling and education about the expected course of concussion recovery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Of the 25 studies, most ( k = 19, 76%) did not find that pre-injury migraines were a risk factor for a worse clinical outcome following a sport-related concussion, two studies (8%) had both negative and positive findings, and four studies (16%) had positive findings; of note, one study did not conduct statistical analyses, ( 33 ) but based on the raw data reported in the paper, we conducted chi-squared tests and the p -values were >0.05; this study was included as one of the 19 studies with null results. Across all studies, 24% ( k = 6/25) reported at least one result (e.g., symptom duration, time to return to play) showing an association between pre-injury migraine history and worse clinical outcome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 25 studies, most ( k = 19, 76%) did not find that pre-injury migraines were a risk factor for a worse clinical outcome following a sport-related concussion, two studies (8%) had both negative and positive findings, and four studies (16%) had positive findings; of note, one study did not conduct statistical analyses, ( 33 ) but based on the raw data reported in the paper, we conducted chi-squared tests and the p -values were >0.05; this study was included as one of the 19 studies with null results. Across all studies, 24% ( k = 6/25) reported at least one result (e.g., symptom duration, time to return to play) showing an association between pre-injury migraine history and worse clinical outcome.…”
Section: Resultsmentioning
confidence: 99%
“…It is essential to appreciate that only one study was designed specifically to examine migraine as a risk factor ( 45 ). All other studies included migraine as a secondary or exploratory variable; some studies discussed their rationale for examining pre-injury migraines ( 10 , 20 , 34 37 , 41 43 , 46 ), while others did not ( 13 , 14 , 16 19 , 21 , 30 , 32 , 33 , 38 40 , 44 ). Most studies ( n = 19/25, 76%) did not find a statistically significant association between having pre-injury migraines and a prolonged recovery or worse clinical outcome following concussion, two studies had both significant and null findings, and four studies showed only significant findings.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, after a period of short rest, some of the current guidelines recommend 'relative rest and exercise' for SC (Patricios et al 2023, p. 71) or 'active recovery' (Australian Institute of Sport 2023, p. 35). This form of recovery for SC is now known to benefit patients (Neidecker et al 2021). The idea of relative rest supports an ongoing break from high-risk activities and exercise (such as contact sports) while other activities and exercises are gradually resumed.…”
Section: Introductionmentioning
confidence: 99%